Against Discrimination - Aprilian Sumodiningrat; Jihan Arsya Nabila (Journal of Contemporary Sociological Issues, 2022)
Racial discrimination and violence against minority communities are prohibited by law, and the protection of these minority groups is protected by the Constitution, national laws, and international laws or conventions ratified by Indonesia, such as ICCPR, and ICERD. Violence cases involving ethnic Papuans are a form of human rights violation that is often ignored by the state. This study will use the normative juridical approach method, by presenting and analyzing the validity of the provisions of the legislation. Socio-legal studies, in this study, will be conducted by conducting an analysis of social studies, the theory of multidisciplinary theory of social sciences, related to the phenomenon of racial discrimination against ethnic Papuans, such as Psychological science in looking at a guess, to discrimination; communication science; Theory of Social Integration and Disintegration; and Social Conflict Theory. The aim of this study was to examine law enforcement, using paradigms in the social sciences. In this study, it will be reviewed on the quality of law enforcement, the extent to which the rules are enforced, as well as the extent to which law enforcement, as well as the government, can fulfill the rights of citizens not to discriminate in it. This research shows that discrimination against the Papuan people is caused by racial discrimination in various aspects, economic, political, educational, law enforcement, etc. The application of anti-discrimination law must be based on the professionalism of law enforcement officers, so as not to cause new discrimination in law enforcement. This study recommends that the Government of Indonesia to further increase political will in the enforcement of anti-discrimination and violence laws in all cases, especially against Papuan ethnic groups. Maximum anti-discrimination law enforcement efforts are needed to realize human rights goals, namely the fulfillment, enforcement, and protection of human rights. Keywords: Discrimination, Minority, Human Rights, Papua, Politics